Occupational Exposure to Bloodborne Pathogens Among Nurses, Dental Staff, and Health Security Workers-An Updated Review - Majmi, Ahmed Jardi Ali; Khalil Mohammed Khalil Aldhuwaymir; Abdullah Ali Nasser Alshehri; Monirah Salem Alharbi; Hanan Faris Ahmed Muswadi; Basmah Abdulelah Abdullah Madkhali; Yara Abduh Ali Sultan; Nemat Nour Allah Qari; Abdulaziz Salman Almukhalfa; Jawaher Mohammed Abkar Zailai; Fatimah Ibrahim Ali Sharwani; Wejdan Abdullah Ahmed Ali; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Occupational exposure to bloodborne pathogens remains a significant hazard for healthcare workers despite the implementation of global safety standards such as the OSHA Bloodborne Pathogens Standard. Nurses, dental staff, and health security workers are particularly vulnerable due to frequent contact with blood and body fluids, increasing the risk of transmission of HIV, HBV, and HCV. Aim: This review aims to synthesize updated evidence on occupational exposure risks, regulatory frameworks, preventive strategies, and ongoing challenges among nurses, dental personnel, and health security workers. Methods: A narrative updated review approach was used, analyzing regulatory guidelines, epidemiological data, and recent literature on occupational exposure, infection control practices, and preventive interventions in healthcare settings. Results: Findings indicate that needlestick injuries and sharps-related incidents remain the primary route of exposure. HBV, HCV, and HIV continue to represent the most clinically significant pathogens. Despite vaccination programs, engineering controls, and training initiatives, compliance gaps, underreporting, inconsistent PPE use, and suboptimal adherence to standard precautions persist. Economic burden and psychological distress among exposed workers remain substantial. Conclusion: Occupational exposure to bloodborne pathogens continues to pose a multidimensional challenge requiring strengthened compliance, improved training, and system-wide safety culture. Interprofessional collaboration and strict adherence to OSHA standards are essential for reducing risk.